A time-dependent model for seismic risk reduction policy analysis - Rabonza, Maricar (2023)
The seismic risk of cities is constantly changing as cities themselves evolve in time. Key to making informed policy decisions to promote resilient cities is the ability to futurecast the risk of cities based on such potential policy decisions. This work demonstrates a flexible stochastic framework for analysing the potential seismic risk trajectories of cities. The model can be used to better understand how various retrofit policy standard and implementation time-frames affect seismic risk over time. Each policy or combination of policies can be compared with each other, and with the baseline case of “doing nothing.” The model therefore serves as a seismic risk reduction policy analysis tool, and also as an advocacy tool, demonstrating that “the risk of doing nothing” is itself a policy decision, usually with the worst of possible consequences. The framework is demonstrated with a hypothetical case-study, which can serve as template for the analysis of real cities.